Influence of ambient temperature on plasma ammonia and lactate accumulation during prolonged submaximal and self-paced running - Marino, F. E.; Mbambo, Z.; Kortekaas, E.; Wilson, G.; Lambert, M. I.; Noakes, T. D.; Dennis, S. C. (European Journal of Applied Physiology, 2001)
This study examined the effects of heat stress on the accumulation of plasma ammonia, lactate, and urate during prolonged running. Nine highly trained endurance runners completed two running trials in a counterbalanced fashion in cool (15°C) and in hot (35°C) humid (60% relative humidity) conditions. Subjects ran on a motorised treadmill at 70% of peak treadmill running speed for 30 min (submaximal) followed by a self-paced 8-km performance run. Blood was drawn at pre-exercise, end-submaximal and end-performance run and analysed for plasma ammonia, lactate, and urate. Four subjects failed to complete the performance run in the heat and the performance times for the rest of the subjects was increased from 27.3 (0.6) min in cool conditions to 31.3 (1.2) min in hot conditions (P<0.05). The end-performance rectal temperature was 38.6 (0.1) and 39.2 (0.1)°C (P<0.05) in cool and hot conditions, respectively. Differences in plasma lactate at the end of submaximal running were not significant. However, at the end of performance runs lactate was 6.0 (0.9) mmol·l-1 in cool and 3.1 (0.5) mmol·l-1 in hot conditions, values that were significantly different (P<0.05). Plasma ammonia increased from pre-exercise to 59 µmol·l-1 at the end-submaximal runs for both coditions and further at the end of performance runs to 108.5 (11) µmol·l-1 (P<0.05) in hot but not in cool conditions. Plasma urate increased from pre-exercise to 311.2 (25.9) µmol·l-1 at end-submaximal runs and to 320.4µmol·l-1 at end-performance runs in hot and cool environments. The findings that plasma urate accumulation was similar at the completion of running in both conditions, while ammonia was significantly augmented in hot conditions compared with cool, suggest that ammonia accumulation during heat stress exercise might be derived from sources other than purine catabolism.